THE INFLUENCE OF EARNINGS MANAGEMENT ON CORPORATE RISK WITH ESG AS A MODERATION VARIABLE - Jesicha Hilery Br Ginting; Amrie Firmansyah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
The low quality of financial reporting due to earnings management practices can increase information uncertainty, reflected in the volatility of stock returns as an indicator of corporate risk. On the other hand, the application of Environmental, Social, and Governance (ESG) principles is expected to increase transparency, accountability, and the quality of corporate governance, thereby mitigating risks arising from opportunistic management behavior. However, empirical evidence on the role of ESG in moderating the relationship between earnings management and corporate risk, particularly in the banking sector in post-pandemic Indonesia, is still limited. This study aims to examine the influence of earnings management on corporate risk, proxied by stock return volatility, and to analyze the role of ESG disclosure as a moderating variable in banking companies listed on the Indonesia Stock Exchange for the 2022-2024 period. The study used a quantitative method and purposive sampling, yielding 120 company-year observations from 40 banking companies. Hypothesis testing was performed using a panel data multiple linear regression. The study's results show that earnings management does not significantly affect stock return volatility. Moreover, ESG disclosures are not able to moderate the relationship between earnings management and corporate risk. These findings indicate that the volatility of stock returns in banking firms during the observation period was influenced more by factors beyond earnings management practices and ESG disclosures. The implications of this study emphasize the importance of strengthening the quality of ESG implementation, financial reporting transparency, and corporate governance to support more effective risk management.